2016
DOI: 10.1111/nmo.12807
|View full text |Cite
|
Sign up to set email alerts
|

Potential association of VAMP5 polymorphisms with total colonic aganglionosis in Hirschsprung disease

Abstract: Considering that differential genetic effects on the development of the enteric nervous system, our results suggest that VAMP5 may be associated with the TCA of HSCR. However, further replications and functional evaluations are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
(57 reference statements)
1
4
0
Order By: Relevance
“…SNPs rs10206961 and rs14242 in VAMP5 shows significant association with HSCR (0.044≤P_adj≤0.046, 1.12≤OR≤1.17 for rs10206961; P_adj=0.020, OR=1.20 for rs14242). Inconsistent with the report by Shin JG et al [ 12 ] for the SNP rs1254900 in VAMP5 , we failed to replicate the association in our population (0.666≤P≤0.953, 0.97≤OR≤1.04 for rs1254900). For the most prominent SNP rs11241200 in MCC , 0.282≤P≤0.438 for rs11241200, we failed to replicate the association as presented previously [ 17 ].…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…SNPs rs10206961 and rs14242 in VAMP5 shows significant association with HSCR (0.044≤P_adj≤0.046, 1.12≤OR≤1.17 for rs10206961; P_adj=0.020, OR=1.20 for rs14242). Inconsistent with the report by Shin JG et al [ 12 ] for the SNP rs1254900 in VAMP5 , we failed to replicate the association in our population (0.666≤P≤0.953, 0.97≤OR≤1.04 for rs1254900). For the most prominent SNP rs11241200 in MCC , 0.282≤P≤0.438 for rs11241200, we failed to replicate the association as presented previously [ 17 ].…”
Section: Resultssupporting
confidence: 58%
“…More specifically, genetic variants of VAMP5 may functionally hinder the normal the migration and proliferation of enteric neural crest cell. Similar genetic studies have suggested that there was a relationship between VAMP5 polymorphisms and HSCR [ 12 ]. Three SNPs in VAMP5 overlaps with the previously reported potential association of VAMP5 polymorphisms with 21 TCA patients [ 20 ].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…It encodes synaptobrevin, a member of the soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) protein complex. In the GWAS studies five SNPs (rs10206961, rs1561198, rs1254900, rs55971080, and rs14242) of VAMP5 and three haplotypes including BL1_ht1, BL2_ht1,and BL2_ht2 were significantly potential risk for TCA in HSCR [Shin et al, 2016]. Additionally another GWAS study identified 13 SLC6A20 SNPs that were significantly associated with HSCR, even following correction for multiple comparisons.…”
Section: Genes and Variations Associated With Risk Of Hscrmentioning
confidence: 99%
“…25,34,43 Furthermore, vesicle-associated membrane protein 5 rs1254900 and mutated in colorectal cancer rs11241200 contributed to the risk of HSCR by logistic regression and multifactor dimensionality reduction analyses in southern Chinese children and the Korean population. 27,44 These studies mentioned above indicate that SNPs may affect expression and function of target genes and may contribute to susceptibility of HSCR. Nonetheless, additional studies are required to improve the knowledge about the role of epigenetics in the pathogenesis of HSCR.…”
Section: Discussionmentioning
confidence: 99%